Virtual Screening the Interaction of Various Compound from Indonesian Plants with the HGXPRT Enzyme to Find a Novel Antimalarial Drug - Wilda Nur Rohmatillah; Naura Bathari Winarto; Arthur Hariyanto Prakoso; Bawon Triatmoko; Ari Satia Nugraha (Future Science)
Medicinal plants have been a notable source for antimalarial agents. This study was aimed to investigate the antimalarial potency of Indonesian medicinal plants used traditionally in malarial fever therapy. A total of 238 compounds derived from 43 plants traditionally used to alleviate malarial fever were collected and loaded into molecular docking protocol. The compounds were screened against Hypoxanthine-Guanine-XanthinePhosphoribosyltransferase (HGXPRT, 3OZF) using the AutoDock Vina software 1.1.2. The compound is important for the purine synthesis of the parasite. The experiment resulted in AM125 (20-isoveratramine) from Cyanthillium patulum to possess the highest affinity with free energy (?G)-11 kcal/mol, which is better than HGXPRT native ligands (-6.4kcal/mol). This suggested Cyanthillium patulum was a potential source for antimalarial agents in which its constituents, 20-isoveratramine might responsible for the claims.